Appointment of Brother J. Benedict FSC - De La Salle University, Manila (Animo Repository, 2002)
The Office of the President announced the appointment of Brother J. Benedict, FSC as Vice President Emeritus for Development and Alumni Affairs of the DLSU System. Occupying his vacated post is Jose Kalaw.